Perjanjian Oligopoli dan Asas Keseimbangan dalam Persaingan Usaha Berdasarkan Undang-Undang Nomor 5 Tahun 1999 BUSINESS COMPETITION BASED ON LAW NUMBER 5 OF 1999 - Gede Darwis Triadi; Johannes Ibrahim Kosasih; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
An oligopoly agreement is a form of agreement in which business actors own all kinds of objects and activities. The existence of this agreement requires a principle of balance in doing business in protecting others in carrying out quality and balanced economic enterprises based on applicable regulations. The purpose of this study is to determine the principle of balance that must be carried out against sellers in relation to the existing regulations, knowing the practice of the oligopoly agreement associated with Law Number 5 Year 1999, knowing Law No. 5 of 1999, and efforts to anticipate the occurrence of Oligopoly agreement practices and accommodate the principle of balance. The method used in this research is normative legal research. The results show that the principle of balance between business actors is associated with the enforcement of Law Number 5 of 1999, namely Protecting small businesses, maintaining healthy competition, and economic efficiency. Meanwhile, the practice of oligopoly agreements has a huge impact on consumer losses and among business actors, and in article 4 of law number 5 of 1999, oligopoly agreements are prohibited if they can harm competition. So that the anticipation efforts that can be made against the traffickers with a system of compliance and implementation of obligations as well as managing a relationship with the provider of the spreader and the user which must agree with the regulations.